In Silico Evaluation of Diterpenoids from Jatropha curcas Roots as Potential HMG-CoA Reductase Inhibitors for Hyperlipidemia Management - Ritu Kumari Singh,; Nitesh Chandel,; Dr. Dhaval Patel,; Dr. Pankti Dalwadi,; Ketan Rathod, (Asian Journal of Pharmaceutical Research and Development, 2026)
Hyperlipidemia is a major metabolic disorder characterized by elevated levels of cholesterol and triglycerides, predisposing individuals to atherosclerosis and cardiovascular diseases. Although statins remain the first-line therapy through inhibition of 3-hydroxy-3-methylglutaryl-coenzyme A (HMG-CoA) reductase, their long-term use is associated with adverse effects, including hepatotoxicity and myopathy. This has fueled interest in identifying safer, plant-derived alternatives. Jatropha curcas, a medicinal plant traditionally used for various ailments, is particularly rich in bioactive diterpenoids in its root extracts. These secondary metabolites exhibit a wide spectrum of pharmacological properties, yet their potential in lipid-lowering therapy remains underexplored.The present study aimed to evaluate the binding affinity and interaction profile of selected diterpenoids from J. curcas roots against HMG-CoA reductase using molecular docking. Ligands were retrieved from published phytochemical reports and optimized, while the crystal structure of HMG-CoA reductase (PDB ID: 1HWK) was prepared by removing water molecules and heteroatoms. Docking was performed using AutoDock Vina, and results were visualized with Discovery Studio. Among the tested compounds, [ Curcusone B] exhibited the lowest binding energy (-9.1 kcal/mol), forming stable hydrogen bonds with key active site residues such as Lys735, Glu559, and Ser684, comparable to the reference drug atorvastatin. Other diterpenoids such as [Jatropholone B (-8.9 kcal/mol)] also demonstrated favorable interactions, suggesting their potential as natural HMG-CoA reductase inhibitors. These findings highlight the promise of J. curcas diterpenoids as lead candidates for hyperlipidemia management, providing a strong rationale for further in vitro and in vivo validation. Overall, this study emphasizes the relevance of in silico approaches in accelerating the discovery of plant-based lipid-lowering agents.